Effects of Firm Size, Audit Opinion, and Financial Difficulty on Auditor Change in Infrastructure Companies Listed on the Indonesian Stock Exchange Over the Period 2017-2021 - Liahmad, Liahmad; Rahman, Taufiqur (Majapahit Journal of Islamic Finance and Management, 2025)
The importance of auditor independence in performing audit work has led many companies to change auditors to maintain their independence. This study aims to identify empirical evidence regarding factors that influence auditor turnover, such as firm size, financial condition, and audit opinions. This research is quantitative, with data sources drawn from the Indonesian scholarship. The population used was infrastructure companies listed on the Indonesian stock exchange for the period 2017–2021. Thirty-one infrastructure companies served as the sample. The research sample was obtained using purposive sampling technique. The analytical method used was logistic regression analysis. The results showed that firm size, financial condition, and audit opinion do not influence auditor switching.